“THAT WE COULDN’T TURN OUR EYES AWAY”. COURTLY CULTURE IN PEREGRYNACJA MAĆKOWA - Wojtowicz, Witold (Prace Polonistyczne, 2021)
Referring to my previous research (Wojtowicz 2010, 2011), the article analyses a humorous text entitled Peregrynacja Maćkowa (Maciek’s Peregrination, printed in 1612) which offers a parodic and satirical take on the ideas characteristic of courtly culture. I examine how these ideas are mocked with the use of parodic travesty. What serves as a starting point for discussion are the analyses of courtly culture by Rüdiger Schnell (in Die höfische Kultur des Mittelalters zwischen Ekel und Ästhetik). Apart from parodying courtly culture, the author of Peregrynacja Maćkowa mocks the chivalric romance and travel novels as well as alludes to the Brautwerbung motif.